Job satisfaction among nurses in Al-Qassim hospitals and primary health care centers, Saudi Arabia, 2016 - Al-Takroni, Hassan; Al-Hindi, Adel; Joshva, kavija; Al-Harbi, Awad (International Journal of Advanced Nursing Studies, 2018)
Background: Job's satisfaction consists of a feeling of well-being, resulting from the interaction of several occupational aspects, and may influence the worker's relationship with the organization, clients and family. Hence, it becomes important than the quality of nursing care to reflect on this topic in depth. The current nursing shortage and high turnover are of great concern in the Kingdom of Saudi Arabia (KSA) because of its impact on the efficiency and effectiveness of any health-care delivery system. Objectives: To assess the level of job satisfaction among staff nurses working in Ministry of Health(MOH) hospitals and primary health care centers (PHC) in Al Qassim region. To prepare and implement an action plan according to the findings from the study.Methods: A descriptive cross- sectional design is utilized in the current study. The study was conducted between 5542 nurses working in 20 hospitals and PHCs in Al Qassim region. Response rate is 18% and 1037 questionnaires were analyzed using factor analysis and correlation.Findings: Overall results show that the job satisfaction is found to be averagely satisfied. Accommodation level, administration, work condition, recognition, co-workers communications, educational activity, payment, vacation and leave are used to determine the job satisfaction. There is no correlation between demographic variables and job satisfaction among the staff nurses. Most of the staffs were not satisfied with the workload. Additionally, most of the nurses not satisfied with their weekly off, and they are not happy with their annual allowance.Conclusion: This study concluded that the majority of the nurses participated in the study are averagely satisfied in their job. Therefore, the administration needs more interventions to build the satisfaction of staff nurse for better nurse retention.